1997
DOI: 10.1073/pnas.94.18.9967
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxin A4stable analogs inhibit leukocyte rolling and adherence in the rat mesenteric microvasculature: Role of P-selectin

Abstract: Three different stable lipoxin A 4 (LXA 4 ) analogs (i.e., 16-phenoxy-LXA 4 -Me, 15-cyclohexyl-LXA 4 -Me, and 15-R/S-methyl-LXA 4 -Me) were studied for their ability to modulate leukocyte-endothelial cell interactions in the rat mesenteric microvasculature. Superfusion of the rat mesentery with 50 mol/liter N G-nitro-L-arginine methyl ester (L-NAME) caused a significant, time-dependent increase in leukocyte rolling (56 ؎ 8 cells/min; P < 0.01 vs. control) and leukocyte adherence (12.5 ؎ 1.2 cells/100 m length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 35 publications
1
87
0
Order By: Relevance
“…In particular, they block chemotaxis and adherence to microvasculature, inhibit nuclear factor-kB activation in leukocytes, and block the release of proinflammatory cytokines such as interleukin-6, interleukin-8, and tumor necrosis factor-a. 16,[35][36][37][38] A potential limitation of our study is that microgram quantities of ATL were required to limit lung injury in our experiments, whereas others have reported that nanogram amounts of proresolving lipid mediators For personal use only. on March 28, 2019.…”
Section: Discussionmentioning
confidence: 68%
“…In particular, they block chemotaxis and adherence to microvasculature, inhibit nuclear factor-kB activation in leukocytes, and block the release of proinflammatory cytokines such as interleukin-6, interleukin-8, and tumor necrosis factor-a. 16,[35][36][37][38] A potential limitation of our study is that microgram quantities of ATL were required to limit lung injury in our experiments, whereas others have reported that nanogram amounts of proresolving lipid mediators For personal use only. on March 28, 2019.…”
Section: Discussionmentioning
confidence: 68%
“…11 However, the rank order of cysteinyl LTs in inducing surface expression of P-selectin, a well-characterized vascular action of cysteinyl-LT, and the inability of selective CysLT 1 receptor antagonists to inhibit this response suggest that these endothelial receptors are likely distinct from CysLT 1 . 16,24,25 Although the CysLT 1 receptor was identified and cloned by other investigators, 14,18 it was not formally cloned or identified from human vascular endothelial cells. The available evidence that this receptor was indeed a major endothelial receptor remained incomplete.…”
Section: Resultsmentioning
confidence: 99%
“…7,8 Although inflammation is a life-saving process and must be highly efficient against bacteria invasion, "inflammation from within"-that is, in the vasculature-must be tightly controlled to avoid widespread damage. Thus, low doses of LXA 4 inhibit polymorphonuclear cells (PMN) accumulation both in postischemic mesenteric tissues 9,10 and in distant organs such as the lung 11 ; similarly, AnxA1 and erythropoietin are potent inhibitors of myocardial infarct, stroke, and vascular reperfusion injury. [12][13][14] In situations where reperfusion occurs, such as renal transplantation, LXA 4 15 and resolvins 16 are highly protective, and the same has been reported recently for AnxA1 mimetics.…”
Section: Introductionmentioning
confidence: 99%